Schema influence on listening and speaking input retention - Ernisa, Marzuki; Ahmed Shamsul Bahri, Mohamad Tuah; Salina, Pit; Faidz Felani, Majeri (Issues in Language Studies, 2013)
Schema has been shown to influence reading and listening processes and retention of information. At the same time, it also arguably resists new information. This study aimed to find out the level of specific item recall in participants after they were given either a listening or reading input with specific altered items. It also examined the differences in the retention of participants who possessed schema of the narrative compared with those who did not possess the schema. For the specific item recall, results revealed that regardless of the type of input, the four major altered items were recalled the most. Meanwhile, the comparison between participants with schemata and without schemata showed that those with schema performed better, with participants who listened to the input and possessing schema achieving the best retention results. The results of this study highlighted the importance of narrative selection for input in teaching and learning whilst also providing evidence that cultural schema influences the type of items recalled from both types of input.